Recent Advances in Catalytic Oxidation of Organic Sulfides: Applications of Metal–Ionic Liquid Catalytic Systems - Liu, Xiao Bing; Rong, Qi; Tan, Jin; Chen, Chen; Hu, Yu Lin (Frontiers in Chemistry, 2022)
Catalytic oxidation of organic sulfides is of considerable significance in industrial chemistry and fuel industry. Therefore, numerous methods have been developed for the oxidation. Metal-containing ionic liquid-based catalysts can catalyze the selective oxidation reactions and are highly used in chemical processes, which have also been used as effective solvents, reaction media, extractants, and catalysts for the oxidation of organic sulfides including oxidative desulfurization of fuel oil. Recently, much attention is being drawn to the preparation of heterogenous catalysts based on the immobilization of metal- or nonmetal-containing ILs on diverse solid supports, which can be easily separated after the completion reaction and recycled. Therefore, there is still an increasing interest in developing new and efficient catalytic procedures for the oxidation of organic sulfides. In this review, we have outlined the recent advances in catalytic oxidation of organic sulfides including oxidative desulfurization of fuel oil. The versatilities and adaptabilities of metal–ionic liquid catalytic systems in the selective oxidation of sulfides are considered a powerful research field in these transformations.